STRATEGI DAKWAH GENERASI MILENIAL: Studi Kasus Rutinan Minggu Legi (Ngaji dan Maulid Diba’) STAIMU Mukomuko - Ahmad Atho’ul Karim; Fauzia Nuraziza (Al-Idaroh: Media Pemikiran Manajemen Dakwah, 2024)
An effective da'wah strategy for millennials must be tailored to their unique characteristics, interests and habits. Millennials spend a lot of time on social media such as Instagram, Twitter, YouTube and TikTok. Therefore, using these platforms to deliver da'wah messages is very effective. This research activity is intended to find out how the da'wah strategy activities used in the Sunday Legi Routine (Ngaji and Maulid Diba') at STAIMU Mukomuko. This research uses a descriptive qualitative approach. The results of this study are; da'wah strategies that utilise digital technology, present relevant content relevant content, and using musical approaches such as hadroh Sapu Jagat is very effective for the millennial generation. Routine Sunday Legi activities at STAIMU Mukomuko has succeeded in increasing participation, satisfaction, and understanding of religious teachings. participants' understanding of religious teachings. The use of social media and digital platforms allows da'wah messages to reach a wider and more diverse audience, especially millennials who are active in the diverse audience, especially millennials who are active in cyberspace. Content relevant to contemporary issues such as mental health, social relationships, and careers, makes religious teachings easier to understand and apply in daily life. makes religious teachings easier to understand and apply in daily life. In addition, interactive approaches, such as group discussions and Q&A sessions, provide opportunities for participants to participate in the programme. Q&A sessions, provide opportunities for participants to actively participate, ask questions, and share their views, which enriches their learning experience. Strategi dakwah yang efektif untuk generasi milenial harus disesuaikan dengan karakteristik, minat, dan kebiasaan unik mereka. Generasi milenial menghabiskan banyak waktu di media sosial seperti Instagram, Twitter, YouTube, dan TikTok. Oleh karena itu, menggunakan platform ini untuk menyampaikan pesan dakwah sangat efektif. Kegiatan penelitian ini dimaksudkan untuk mengetahui bagaimana kegiatan strategi dakwah yang digunakan pada Rutinan Minggu Legi (Ngaji dan Maulid Diba’) di STAIMU Mukomuko. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Hasil dari penelitian ini yaitu; strategi dakwah yang memanfaatkan teknologi digital, menyajikan konten yang relevan, dan menggunakan pendekatan musik seperti hadroh Sapu Jagat sangat efektif untuk generasi milenial. Kegiatan Rutinan Minggu Legi di STAIMU Mukomuko telah berhasil meningkatkan partisipasi, kepuasan, dan pemahaman peserta terhadap ajaran agama. Penggunaan media sosial dan platform digital memungkinkan pesan dakwah menjangkau audiens yang lebih luas dan beragam, terutama milenial yang aktif di dunia maya. Konten yang relevan dengan isu-isu kontemporer seperti kesehatan mental, hubungan sosial, dan karier membuat ajaran agama lebih mudah dipahami dan diaplikasikan dalam kehidupan sehari-hari. Selain itu, pendekatan interaktif, seperti diskusi kelompok dan sesi tanya jawab, memberi kesempatan bagi peserta untuk berpartisipasi aktif, mengajukan pertanyaan, dan berbagi pandangan, yang memperkaya pengalaman belajar mereka.